Jason Compson's invisible life: illocutionary logic in The Sound and the Fury. Issue 5 (28th July 2016) - Shapiro, Brendan
ABSTRACT: This article reads the character of Jason Compson, from William Faulkner's The Sound and the Fury, through the philosopher John Searle's theories of speech acts and social ontology. I will claim that Jason's narrative, a putatively simple section in a famously difficult modernist novel, contains degrees of complexity that become fully apparent only when viewed through a lens that can account for both its distinctive speech forms and the social entities that feature in its plot. Attending to illocutionary form permits us to see how the performative language of Faulkner's section connects speech acts, financial instruments, and institutional structures, and does so in a manner that embeds those abstract entities in the concrete affective space of an individual mind. Ultimately, I suggest that Faulkner's 'simplest' chapter offers an alternative pathway for tracking modernist fiction's stylistic engagement with its institutional milieu.